The Role of Oxidative Stress and Inflammation in Prediabetes: A Review - S.A Saghir, Fatma; Ibrahim, Farrah Shafeera; Amom, Zulkhairi; Othman, Lekhsan (Malaysian Journal of Medicine and Health Sciences, 2023)
Prediabetes is a condition in which blood glucose level is above the normal but below the diagnostic value of diabetes mellitus. Hyperglycaemia can upregulate markers of chronic inflammation and contribute to the overproduction of reactive oxygen species (ROS), which ultimately causes increased oxidative stress. This leads to beta-cell dysfunction and insulin resistance, which are involved in the pathogenesis of prediabetes status. Proper treatment of hyperglycaemia, inhibition of ROS overproduction, and suppression of inflammation are crucial for delaying the onset of diabetes. Therefore, it is essential to determine and understand the mechanisms involved in prediabetes. This review discusses the relationship between oxidative stress and prediabetes, along with the inflammation’s role in prediabetes. Additionally, the effects of some biomarkers of oxidative stress in prediabetes, inflammatory markers, and their influence on chronic inflammation are also briefly reviewed. Finally, the role of antioxidant and anti-inflammatory markers are discussed.